Reduced adrenal stress response in patients on PCSK9 inhibitor therapy. (May 2021) - Meier, Simon; Frick, Marcel; Liu, Michael; Saeedi Saravi, Seyed Soheil; Montrasio, Giulia; Preiss, Helga; Pasterk, Lisa; Bonetti, Nicole; Egloff, Michael; Schmid, Hans-Rudolf; Sudano, Isabella; Camici, Giovanni G.; et al.
Abstract: Background and aims: Treatment with proprotein convertase subtilisin-kexin type 9 inhibitors (PCSK9i), in addition to statin therapy, reduces LDL-cholesterol (LDL-c) in some patients to extremely low levels (i.e.< 20 mg/dl or < 0.52 mmol/l). There is concern that at such low levels, the physiologic role of cholesterol may be impaired, e.g. the adrenal cortisol stress response might be compromised. We therefore evaluated the effect of PCSK9i therapy on the cortisol response to ACTH in patients with LDL-c down to extremely low levels. Methods: Nineteen patients on PCSK9i therapy and 18 controls matched for age, gender and comorbidities were included. The cortisol response to adrenocorticotropic hormone (ACTH) was tested after application of 250 μg ACTH. Results: LDL-c levels ranged from 0.42 to 3.32 mmol/l (mean 1.38 ± 0.84 mmol/l) in the PCSK9i group and 0.81–4.82 mmol/l (mean 2.10 ± 0.97) in the control group. By analysis of covariance (ANCOVA), the PCSK9i group had significantly lower cortisol response compared to the control group (- 97.26 nmol/l, −178.60 to −15.93, p = 0.02) after 60 min. There was a significant positive correlation between the duration of PCSK9i treatment and cortisol levels (r = 0.59, p = 0.009). Extremely low LDL-c levels down to 0.42 mmol/l were not associated with lower stimulated cortisol levels. Conclusions: Patients on PCSK9i therapy showed a significantly lower cortisol response to ACTH. Stimulated cortisol levels were lower in the first months of PCSK9i treatment, suggesting an adaptive phenomenon. We conclude that the adrenal stress response in patients on PCSK9 inhibitor therapy is reduced. Graphical abstract: Image 1 Highlights: Adrenal stress response in patients on PCSK9i therapy was significantly reduced. Stimulated cortisol levels were lower in the first months of PCSK9i treatment. LDL-c down to 0.42 mmol/l was not associated with a reduced adrenal stress response. No difference was found between patients on Alirocumab and Evolocumab.